(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article analyzes the specific characteristics of children with dysgraphia in primary education and explores scientifically grounded methods for their effective instruction and support. Dysgraphia, a neurological-based writing disorder, affects handwriting, spelling, and written expression. The article emphasizes the importance of early diagnosis, the application of multisensory approaches, targeted writing interventions, and the integration of digital technologies to facilitate academic success and personal development in students with dysgraphia.